ETR 300 : Miracle Container Sdn. Bhd. / Sakina Che Sab ... [et al.] - Che Sab, Sakina; Azmi, Norhanani; Ismail, Ramlah; Othman, Siti Noor Zawiyah; Abu Bakar, Noraini (2002)
Miracle Container Sdn. Bhd was established as trading and it's business transaction involved directly to the customers. This business was registered under the partnership agreement. We were encouraged to enter in this business of the increasing population from time to time in our country. We will start operating our business on 1st January 2004. We choose this particular business name (Miracle Container Sdn Bhd) because Miracle is stand for something that are not expected/unbelievable while Container stand for container itself We are trying to achieve professional qualified entrepreneur to give a quality service and make us higher in this type of business ranking in Malaysia. The location of our business is: Miracle Container Sdn.Bhd, Lot 4886, Lorong Mak Mandin 5, Kawasan Perindustrian Mak Mandin, 13400 Butterworth. We selected this particular location by looking on our target market, comprehensive infrastructure such as communication network, transportation, competition and the development of that area. Business that involved selling and renovating containers are rare in Malaysia because of the lack of interest of entrepreneur, especially those who are Bumiputra's. Due to this, a business was form and given the name "Miracle Container Sdn.Bhd'' which related to our business mottos -"Dare to Fail in Reaching the Gains"